The Cultural Value of Sexual Violence - Sellers, Patricia Viseur (Proceedings of the ASIL Annual Meeting, 1999)
Rape, the most commonly committed act of sexual violence, "strikes at the very core of human dignity and physical integrity." Apparently, no societal or political value is presently advanced by partial proscription of rape; neither is justification of legality any longer based on the characterization of the armed conflict or the status of the person. International law - humanitarian law, international criminal law and human rights law - appears to permit no exception or derogation for rape. Contrary to sexual violence's historical "legal" origins, it is the recognition of rape's illegality that best serves the interest of the international community when, in armed conflict, the individual is attacked as a member of the community or the community is attacked through its members.